A new species of Afrohybanthus (Violaceae) from Tamil Nadu, India - Sarvalingam, Ariyan; Ramasubbu, Raju; Punnen, Abraham Bechu; Menaka, Chinnasamy (Phytotaxa, 2025)
Afrohybanthus mahalingamii, a new species of Violaceae described and illustrated from the wasteland and agricultural land area of Pollachi, Coimbatore district, Tamil Nadu, India. This species differs from Afrohybanthus enneaspermus (L.) Flicker in having a stunted habit, unbranched, prominent, densely hirsute stem, ovate or obovate leaf, linear-lanceolate, gland-dotted stipules, hairy sepals with reddish midvein, enlarged and spathulate stigma and a higher number of seeds per capsule. The detailed description, along with diagnostic characters distinguishing closely allied species, conservation status, and colour photographs, is provided.